"Smoker's paradox" in patients with cardiogenic shock complicating myocardial infarction - A substudy of the IABP-SHOCK II-trial and registry. (1st November 2016) - Saad, Mohammed; Fuernau, Georg; Desch, Steffen; Eitel, Ingo; Jung, Christian; Pöss, Janine; Schneider, Steffen; Schuler, Gerhard; Werdan, Karl; Zeymer, Uwe; Thiele, Holger
Abstract: Background: Several studies in patients with acute myocardial infarction (AMI) without cardiogenic shock (CS) indicate a better survival in smokers, the so called "smoker's paradox". For CS, this relationship has not been investigated so far in the primary percutaneous coronary intervention (PCI) era. Methods: In a predefined substudy of the Intraaortic Balloon Pump in Cardiogenic Shock II (IABP-SHOCK II) trial and its accompanying registry including patients with CS complicating AMI we investigated differences in outcome of smokers compared to non-smokers. All-cause-mortality at 1 year was used as primary endpoint. Results: Of 772 patients with available smoking status 263 patients were smokers (34%). Smokers were more often male (79% vs. 65%; p < 0.001), of younger age (61 [interquartile range IQR 52–70] vs. 73 [IQR 64–79] years; p < 0.001), had less comorbidity including arterial hypertension (62% vs. 71%; p = 0.007) and diabetes mellitus (26% vs. 38%; p < 0.001) and had lower levels of serum creatinine (13% vs. 25%; p < 0.001). There was no significant difference between the 2 groups regarding left ventricular ejection fraction, initial revascularization strategy or use of IABP. Smokers had lower rates of mortality at 12 months in univariable analysis (43% vs. 59%; p < 0.001) but not after adjustment for important confounders using Cox-regression analysis (hazard ratio 0.77, 95% confidence interval 0.59–1.03; p = 0.08). Conclusion: Smoking is not predictive of outcome in patients with CS complicating AMI. The observed survival benefit in univariable analysis seems to be explained by the younger age and lower risk profile of smokers. Highlights: Smoking does not predict outcome in CS complicating AMI treated with primary PCI. Survival benefit in univariable analysis relates to the lower risk profile of smokers. Smoker's paradox could not be verified in cardiogenic shock complicating AMI.